Student Response about the Mini Lecture (Cermin) Learning Program Relationship with Student's Learning Intensity in the Field of Islamic Religious Education - Santi Rahayu (International Journal Labs, 2021)
In the current era of globalization, education is very important. If the education of a society develops well, then it is undeniable that the community will be more